Update on the pharmacogenomics of pain management - Kaye AD; Garcia AJ; Hall OM; Jeha GM; Cramer KD; Granier AL; Kallurkar A; Cornett EM; Urman RD (Dove Medical Press, 2019)
Alan David Kaye,1 Andrew Jesse Garcia,2 O Morgan Hall,3 George M Jeha,4 Kelsey D Cramer,4 Amanda L Granier,4 Anusha Kallurkar,5 Elyse M Cornett,5 Richard D Urman61Department of Anesthesiology, LSU Health Sciences Center, New Orleans, LA, USA; 2Department of Anesthesiology, George Washington University School of Medicine and Health Sciences, Washington, DC, USA; 3Department of Anesthesiology, Louisiana State University School of Medicine, New Orleans, LA, USA; 4Department of Anesthesiology, LSU Health Sciences Center New Orleans, New Orleans, LA, USA; 5Department of Anesthesiology, LSU Health Shreveport, Shreveport, LA, USA; 6Department of Anesthesiology, Perioperative and Pain Medicine, Harvard Medical School, Brigham and Women’s Hospital, Boston, MA, USAAbstract: Pharmacogenomics is the study of genetic variants that impact drug effects through changes in a drug’s pharmacokinetics and pharmacodynamics. Pharmacogenomics is being integrated into clinical pain management practice because variants in individual genes can be predictive of how a patient may respond to a drug treatment. Pain is subjective and is considered challenging to treat. Furthermore, pain patients do not respond to treatments in the same way, which makes it hard to issue a consistent treatment regimen for all pain conditions. Pharmacogenomics would bring consistency to the subjective nature of pain and could revolutionize the field of pain management by providing personalized medical care tailored to each patient based on their gene variants. Additionally, pharmacogenomics offers a solution to the opioid crisis by identifying potentially opioid-vulnerable patients who could be recommended a nonopioid treatment for their pain condition. The integration of pharmacogenomics into clinical practice creates better and safer healthcare practices for patients. In this article, we provide a comprehensive history of pharmacogenomics and pain management, and focus on up to date information on the pharmacogenomics of pain management, describing genes involved in pain, genes that may reduce or guard against pain and discuss specific pain management drugs and their genetic correlations.Keywords: pharmacogenomics, pharmacogenetics, pain, anesthesiology, polymorphism, genetics